"I can try and plan, but still get pregnant": The complexity of pregnancy intentions and reproductive health decision-making for adolescents. (July 2021) - Offiong, Asari; Powell, Terrinieka W.; Gemmill, Alison; Marcell, Arik V.
Abstract: Introduction: Teen pregnancy rates have declined in the United States; however, disparities continue to persist particularly among minority, low-income adolescents. A greater understanding of how pregnancy intentions are conceptualized for adolescents, and the role of the social context may illuminate reasons for disparities. The aim of this study was to expand the lens in which adolescents' perspectives of pregnancy are studied by exploring the contextual factors that frame how pregnancy intentions are developed among urban adolescents. Methods: Thirteen focus groups (N = 46) were conducted with male and female adolescents 15–19 years old in Baltimore, Maryland. Participants were recruited from local high schools, and focus groups were stratified by sex and age (15–17 and 18–19). A phenomenological approach was applied to analyze the data both deductively and inductively, allowing for themes to emerge and align within an existing conceptual framework. Results: Two themes identified were stated pregnancy intentions and shared schemas of sex and pregnancy. Participants discussed a range of pregnancy intentions and expressed five social perspectives which informed those intentions: sex is a gendered responsibility, teen pregnancy is cyclical and common, teen pregnancy is not a completely negative experience, having a child fulfills emotional and relational voids, and pregnancy should happen early, just not too early. Conclusion: Pregnancy intentions for adolescents are expansive and driven by complex social perspectives set in their context. More consideration of the context is needed to provide and offer adolescents, particularly those of vulnerable communities, supports that align with their reproductive health needs.